Question
upstudy study bank question image url

6. For each equation, determine whether it has no solutions, one solution, or infinite solutions. If it has one solution, solve to find the value of \( x \) that makes the statement true. Show/explain your reasoning \( \begin{array}{ll}\text { a. } x-4(3-2 x)=3(3 x+4) & \text { b. } x-4(3+2 x)=3(3 x+4) \\ \text { c. } x-4(3-2 x)=3(3 x-4) & \end{array} \)

Ask by Hamilton Vaughan. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

- **a.** No solutions - **b.** \( x = -\frac{3}{2} \) - **c.** Infinite solutions

Solution

To determine whether each equation has no solutions, one solution, or infinite solutions, we will solve each equation step by step. ### a. \( x - 4(3 - 2x) = 3(3x + 4) \) 1. **Distribute** on both sides: \[ x - 12 + 8x = 9x + 12 \] This simplifies to: \[ 9x - 12 = 9x + 12 \] 2. **Rearranging** the equation: \[ 9x - 9x - 12 = 12 \] This simplifies to: \[ -12 = 12 \] Since this statement is false, the equation has **no solutions**. ### b. \( x - 4(3 + 2x) = 3(3x + 4) \) 1. **Distribute** on both sides: \[ x - 12 - 8x = 9x + 12 \] This simplifies to: \[ -7x - 12 = 9x + 12 \] 2. **Rearranging** the equation: \[ -7x - 9x = 12 + 12 \] This simplifies to: \[ -16x = 24 \] 3. **Solving for \( x \)**: \[ x = -\frac{24}{16} = -\frac{3}{2} \] Thus, this equation has **one solution**, \( x = -\frac{3}{2} \). ### c. \( x - 4(3 - 2x) = 3(3x - 4) \) 1. **Distribute** on both sides: \[ x - 12 + 8x = 9x - 12 \] This simplifies to: \[ 9x - 12 = 9x - 12 \] 2. **Rearranging** the equation: \[ 9x - 9x - 12 = -12 \] This simplifies to: \[ -12 = -12 \] Since this statement is always true, the equation has **infinite solutions**. ### Summary of Results: - **a.** No solutions - **b.** One solution: \( x = -\frac{3}{2} \) - **c.** Infinite solutions

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

Alright, let's break down these equations one by one and see what we discover! **a.** Start with the equation: \( x - 4(3 - 2x) = 3(3x + 4) \) Distributing on both sides gives: \( x - 12 + 8x = 9x + 12 \) Combine like terms: \( 9x - 12 = 9x + 12 \) Subtract \( 9x \) from both sides: \( -12 = 12 \) This is a contradiction, which means the equation has **no solutions**. **b.** Now for the second equation: \( x - 4(3 + 2x) = 3(3x + 4) \) Distributing gives: \( x - 12 - 8x = 9x + 12 \) Combine like terms: \( -7x - 12 = 9x + 12 \) Rearranging yields: \( -7x - 9x = 12 + 12 \) Thus, \( -16x = 24 \), so dividing both sides by -16 gives: \( x = -\frac{3}{2} \). There is **one solution**: \( x = -\frac{3}{2} \). **c.** Finally, for the last equation: \( x - 4(3 - 2x) = 3(3x - 4) \) Distributing gives: \( x - 12 + 8x = 9x - 12 \) Combine like terms: \( 9x - 12 = 9x - 12 \) This is an identity, meaning it holds true for all values of \( x \), so there are **infinite solutions**. In summary: - a: No solutions - b: One solution, \( x = -\frac{3}{2} \) - c: Infinite solutions Equations can really put on a show! Always remember to keep an eye out for contradictions or identities that reveal their secrets. Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy